STUDI KELAYAKAN PENDIRIAN INDUSTRI PERMEN JELLY DARI UBI CILEMBU PADA PT GUMMY GEMBIRA - Nainggolan, Willyana Tri Andini; Awanis, Zatalini; Setiawan, Ahmad Dwi; Oktaviani, Nurul; Ariyanto, Krisna; Aviliano, Avil; Yogautami, Radya; Sylvia, Teny; Devita, Wilda Harlia (Journal of Industrial Engineering & Technology Innovation, 2025)
Cilembu sweet potato, a leading Indonesian commodity with natural sweetness and distinctive aroma, has potential to be processed into value-added jelly candies. This study aims to assess the feasibility of developing a Cilembu sweet potato-based jelly candy industry from technical, market, management, location, and economic-financial aspects. The method used is an industrial feasibility study with a descriptive-analytical approach, utilizing primary data on production capacity, machinery requirements, and layout, as well as secondary data from literature and industry standards. Results show a daily production of 115,586 units, COGS of IDR 1,604 per unit, selling price of IDR 2,000 per unit, and profit of IDR 385 per unit. Total fixed costs reach IDR 1.53 billion per month and variable costs IDR 3.33 billion per month. Financial projections indicate a positive net cash flow of IDR 13.26 billion, ROI 24.86%, NPV IDR 84.27 billion, IRR 24%, and B/C ratio 1.9. The project is feasible technically, commercially, and financially, providing added value to local products.